SFRP2 modulates functional phenotype transition and energy metabolism of macrophages during diabetic wound healing - Yang, Jiaqi; Xiong, Guorui; He, Huijuan; Huang, Haili (Frontiers in Immunology, 2024)
Diabetic foot ulcer (DFU) is a serious complication of diabetes mellitus, which causes great health damage and economic burden to patients. The pathogenesis of DFU is not fully understood. We screened wound healing-related genes using bioinformatics analysis, and full-thickness skin injury mice model and cellular assays were used to explore the role of target genes in diabetic wound healing. SFRP2 was identified as a wound healing-related gene, and the expression of SFRP2 is associated with immune cell infiltration in DFU. In vivo study showed that suppression of SFRP2 delayed the wound healing process of diabetic mice, impeded angiogenesis and matrix remodeling, but did not affect wound healing process of control mice. In addition, suppression of SFRP2 increased macrophage infiltration and impeded the transition of macrophages functional phenotypes during diabetic wound healing, and affected the transcriptome signatures-related to inflammatory response and energy metabolism at the early stage of wound healing. Extracellular flux analysis (EFA) showed that suppression of SFRP2 decreased mitochondrial energy metabolism and increased glycolysis in injury-related macrophages, but impeded both glycolysis and mitochondrial energy metabolism in inflammatory macrophages. In addition, suppression of SFRP2 inhibited wnt signaling-related genes in macrophages. Treatment of AAV-SFRP2 augmented wound healing in diabetic mice and demonstrated the therapeutic potential of SFRP2. In conclusions, SFRP2 may function as a wound healing-related gene in DFU by modulating functional phenotype transition of macrophages and the balance between mitochondrial energy metabolism and glycolysis.